2020
DOI: 10.9734/acri/2019/v19i230156
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cause-and-Effect-Analysis for Evaluating Causes of Fire Disasters in Public and Private Secondary Schools in Ilorin Metropolis, Nigeria

Abstract: The contributions of fire disaster to the varying degrees of students’, staff and schools’ property and/or lives lost in secondary schools in Nigeria is recently alarming. The study assessed causes of fire disaster in public and private secondary schools in Ilorin metropolis, Nigeria. The objectives were to identify latent causes of fire disaster, use the fishbone diagram to illustrate and analyze the root-causes of fire disaster in secondary schools. The exploratory research strategy was used. The target popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…At the first stage, a stratified random sampling technique was employed to categorize schools based on the three senatorial districts. As of the time of this report, Kwara central has 101 senior secondary schools, Kwara North 82 and Kwara South 163. schools (Kwara State Ministry of Education, Human andCapital Development, 2019 andIlori, Sawa, andGobir, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…At the first stage, a stratified random sampling technique was employed to categorize schools based on the three senatorial districts. As of the time of this report, Kwara central has 101 senior secondary schools, Kwara North 82 and Kwara South 163. schools (Kwara State Ministry of Education, Human andCapital Development, 2019 andIlori, Sawa, andGobir, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…These conditions lead to the overheating of the electrical wiring, and consequently result in the occurrence of fire (Amuli, 2019). Moreover, the deterioration of the electrical wiring are contributory causes for fires in schools, as deteriorated wiring provides for electrical faults and overheating (Ilori et al, 2019). Further, heat generated from lighting fixtures, equipment and the other appliances in the building facilitates the ignition of the various combustible material, which are usually found in schools (Campbell, 2017).…”
Section: Causes Of Fire Accidents In School Facilitiesmentioning
confidence: 99%
“…Over the years and in recent times, cases of fatal fire disaster have been reported in different parts of Nigeria. For example, in 2015, there was an outbreak break of fire in a public all-girls school in Jogana, Kano state which led to the death ofseven schoolgirls and injured 21 others [4]. The National Emergency Management Agency (NEMA) reported that the mortality rate in Lagos state from 2009 to 2014 was at a mean percentage of 98.4 [5].…”
Section: Introductionmentioning
confidence: 99%